Local heroes. The influence of place of early development in talent development in Danish handball and football - Nygaard Rossing, N. (Aalborg Universitet. Det Sundhedsvidenskabelige Fakultet. Ph.D.-Serien, 2018)
Recent studies have shown that the narrative that the population size of athletes` place of early development play a vital role in their development trajectories, seem to be flawed. Further, since previous studies have investigated community size as a proxy for athletes` place of early development, other proxies may also represent athletes` place of early development in their development to elite. The purpose of this Ph.D. project, comprised of three studies, to examine how players` place of early development influences their development to expertise in Danish handball and football. Odds ratio analysis showed, in the first and second study, that elite youth and elite senior football players were more likely to have grown up in communities of high population density (>1.000 pop./km2) and medium or larger population sizes (<30.000), whereas elite and elite youth handball players most likely had grown up in communities of medium population density (100 to <250 pop./km2) and size (30.000<50.000). A geospatial analysis in the second study showed that elite youth handball and football players primarily had grown up near talent and elite clubs. In the third study, semi-structured interviews with coaches and talent managers presented specific possibilities and obstacles in football players` place of early development at three levels: community, club and team. Participating coaches and talent managers perceived small and remote clubs as obstacles for players` early development. At club level strong leadership, volunteers and good facilities were considered as important aspects that ensured continuing good teams in the local clubs. Further, the participants experienced a somewhat coincidental clustering of talented youth players in clubs with unfavorable conditions at community and club level. The findings from the third study also indicated a linkage between conditions in players` early development environments and how coaches and talent managers perceive talented youth players. The findings of this Ph.D. project suggest that players` players` place of early development is constituted by possibilities within community, club and team level. The findings across studies show that neither a specific community population size or community density seem to be optimal for player development in both Danish handball and football. As such, the findings indicate that the organization of sport is more influential in the Danish player development than the community. However, the clustering of talented players in seemingly coincidental local clubs suggests that team level conditions can outweigh club and community level obstacles. Results also indicate that the identification of talent by coaches and managers is linked to the conditions of the players` place of early development. For instance, players from smaller clubs and rural areas may appear raw as players, since the quality of their training in their local club teams is not as good as players from other clubs.